2005
DOI: 10.1099/mic.0.27499-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Escherichia coli isolates implicated in human urinary tract infection and avian colibacillosis

Abstract: Since avian pathogenic Escherichia coli (APEC) and human uropathogenic E. coli (UPEC) may encounter similar challenges when establishing infection in extraintestinal locations, they may share a similar content of virulence genes and capacity to cause disease. In the present study, 524 APEC and 200 UPEC isolates were compared by their content of virulence genes, phylogenetic group, and other traits. The two groups showed substantial overlap in terms of their serogroups, phylogenetic groups and virulence genotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

31
370
5
18

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 377 publications
(424 citation statements)
references
References 57 publications
(42 reference statements)
31
370
5
18
Order By: Relevance
“…UPEC and APEC strains were investigated for 37 virulence-related genes by multiplex and single PCR assays, as previously described (Johnson & Stell, 2000;Rodriguez-Siek et al, 2005). Targeted genes and their descriptions as well as primer sequences for the amplification procedures are given in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…UPEC and APEC strains were investigated for 37 virulence-related genes by multiplex and single PCR assays, as previously described (Johnson & Stell, 2000;Rodriguez-Siek et al, 2005). Targeted genes and their descriptions as well as primer sequences for the amplification procedures are given in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…These studies have suggested that APEC strains and bacterial human pathogens may show similar adaptations for an extra intestinal lifestyle, with APEC being able to cause disease in humans (Johnson et al 2003, Mokady et al 2005, Rodriguez-Siek et al 2005, Stocki et al 2005. In this study, we analyzed the presence of virulence genes related to adhesion and invasion to eukaryotic cells and tissues and the expression of iron uptake systems, which were originally described to be present in human pathogenic Escherichia coli, Yersinia and Shigella, among pathogenic and commensal avian E. coli strains, and associated these findings to the four major phylogenetic groups of E. coli (A, B1, B2, and D) described by Clermont et al (2000).…”
Section: Discussionmentioning
confidence: 99%
“…Rodriguez-Siek et al (2005) showed that E. coli strains isolates obtained from human urinary tract infections (UTI) and avian colibacilosis could have substantial overlap in terms of serogroups, phylogenetic groups and virulence genotypes, including plasmid-DNA-related sequences, adhesion, iron uptake, protectins and toxins-related sequences. A previous subtractive hybridization analysis with two APEC strains and one E. coli K12 strain (Stocki et al 2002) detected APEC specific DNA fragments presenting high homology with DNA sequences of E. coli O157:H7 and human ExPEC strains.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, several works demonstrated the presence of genetic similarities among APEC strains, human Escherichia coli and other Enterobacteriaceae species, which suggested that APEC strains present a zoonotic risk (Stocki et al 2002, Johnson et al 2003, Mokady et al 2005, Rodriguez-Siek et al 2005. The aim of the present study was to verify if there is a genetic similarity, as determined by the DNA sequencing and comparison of the fliC gene among avian pathogenic E. coli and other strains of human bacterial pathogens such as E. coli, Salmonella enterica, Yersinia enterocolitica, and Proteus mirabilis.…”
Section: Discussionmentioning
confidence: 99%